2016
DOI: 10.1183/13993003.01701-2015
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary mucosa-associated lymphoid tissue lymphoma revisited

Abstract: This general review sought to clarify the pathophysiological, diagnostic, prognostic, and therapeutic features of pulmonary mucosa-associated lymphoid tissue (MALT) lymphoma.MALT lymphoma is the most common pulmonary B-cell lymphoma, which usually occurs in the context of acquired MALT. The disease is slow-growing with an asymptomatic chronic alveolar opacity visible on radiography. Diagnosis requires tissue samples that should be retrieved using minimally invasive techniques, such as bronchoscopy or computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
117
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(120 citation statements)
references
References 96 publications
(155 reference statements)
3
117
0
Order By: Relevance
“…Two patients (10%) had autoimmune disease. These results were similar to those for PML (1,3). The location of the tumor in 14 patients (70%) was the central airway, and 4 patients (20%) had lobar atelectasis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Two patients (10%) had autoimmune disease. These results were similar to those for PML (1,3). The location of the tumor in 14 patients (70%) was the central airway, and 4 patients (20%) had lobar atelectasis.…”
Section: Discussionsupporting
confidence: 88%
“…Gelder et al reviewed 321 primary tracheal tumors and reported that 54.2% were squamous cell carcinoma (SCC), 10.6% were adenoid cystic carcinoma (ACC), and only 4 out of 321 (1.2%) were lymphoma (2). Bronchus-associated lymphoid tissue (BALT) can be found in follicular bronchiolitis and can be associated with various autoimmune disorders, such as Sjögren's syndrome, but is not found in the normal lung (1). When a primary PML develops from BALT, it is known as BALT lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPA has been reported to mask underlying malignancies in a few case reports including haematological malignancies and, rarely, mucosal-associated lymphoid tissue (MALT) lymphoma 9. Often, NPA can be completely asymptomatic and may be diagnosed as an incidentaloma on chest imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Lung mucosa-associated lymphoid tissue (MALT) has been reported, occasionally related to Helicobacter pylori [58,59]. At CT, MALT lymphomas manifest as chronic localized opacities including consolidations, nodules, and masses with the presence of airways within the lesions in 85% [60,61]. After respiratory failure, lymphoma is the second cause of death in CVID [16].…”
Section: Lung Manifestations In Common Variable Immunodeficiencymentioning
confidence: 99%